Acupressure GB 21 JIANJING and LI4 HEGU points for Reducing Anxiety, Labor pain During the Active Phase of the First Stage of Labor in Primiparous Women - kusyani, asri; Fatmawati, Elis; Diana, Alis Nur (Universitas Tribhuwana Tunggadewi, 2026)
Anxiety and labor pain during the active phase of the first stage of labor are common physiological and psychological responses among primiparous women and may adversely affect labor outcomes if not properly managed. Increased anxiety can intensify pain perception through sympathetic activation and catecholamine release. Non-pharmacological interventions, including stimulation of acupressure points such as GB 21 Jianjing and LI 4 Hegu, may help reduce these responses. This study aimed to determine the effect of acupressure at GB 21 (Jianjing) and LI 4 (Hegu) on anxiety and labor pain in primiparous women. A pre-experimental one-group pre-test–post-test design was conducted among 30 primiparous women in the active phase of labor selected through purposive sampling. Inclusion criteria were singleton pregnancy, 37–42 weeks’ gestation, cervical dilatation 4–7 cm, cephalic presentation, absence of obstetric complications, and willingness to participate. Women with high-risk conditions or those who had received prior pharmacological analgesia were excluded. Anxiety was measured using the Hamilton Anxiety Rating Scale (HARS), and pain intensity was assessed using the Numeric Rating Scale (NRS). Data were analyzed using the Wilcoxon signed-rank test with a significance level of p 0.05. Before intervention, 76.7% of respondents experienced severe anxiety and 43.3% reported moderate pain. After acupressure, 43.3% reported mild anxiety and 50% mild pain. Statistical analysis showed significant reductions in both anxiety and pain (p 0.001). Acupressure at GB 21 and LI 4 significantly reduced anxiety and labor pain in primiparous women and may serve as a complementary intervention in maternity care. Further randomized controlled trials with larger samples are recommended.